Mapping Of Potential Areas of Groundwater Zones in the Najaf-Karbala Alluvial Fan Using Remote Sensing and GIS Technology - Albhadili, Suaad; Al-Ali, Ali K.; Karem, Duha S. (Iraqi Journal of Science, 2025)
Geospatial tools like remote sensing and GIS are vital for evaluating, monitoring, and preserving groundwater resources, especially in changing climates. Finding areas where groundwater recharge is most likely is crucial for protecting and managing its quality. In arid regions, groundwater is extracted extensively due to its importance for various uses. This study aims to identify and categorize productive areas for groundwater in Al Najaf – Karbala fan using remote sensing and GIS. The AHP method employed the weight for each factor used to determine the map potential zones, incorporating seven factors: geomorphology, lithology, aspect, drainage density, lineaments density, land cover, and slope. Each factor was ranked and categorized based on its hydrogeology impact on groundwater availability. The results revealed five productivity zones: very low, low, moderate, high, and very high, covering 5%, 10%, 15%, 30%, and 40% of the study area, respectively. Western and southwestern study areas have low potential, while eastern and middle areas have moderate potential. The center and northeastern regions boast the highest potential.